Designing software for child users: a case study of a web page construction kit for children - Ibrahim, A.A.A.; Salim, S.S. (2004)
User interface design is a part of what users can see, touch, hear and communicate with. To produce software applications that are good, effective and high usability in terms of interface design, the involvement of users are needed in system development especially when designing for children. Almost all of the software applications designed for children are developed by adults based on what they assume children want. As a result, the application may not be easily learned or used by children. There are three goals of this research 1) to know childrenâs abilities and skills in computer usage; 2) to know their problems with the existing kits; and 3) suitable designs for them. This paper describes the prototype of web page construction kit for children as a case study. The requirements are based on interviews with children, analysis of the existing tools and analysis of homepages created by children. The design of the prototype has also been evaluated in order to determine whether or not it is suitable and fulfils the childrenâs requirements. As a conclusion, this paper reveals a few questions that need to be considered in designing childrenâs software.